Experimental testing of stainless steel bolt assemblies at elevated temperatures - Shaheen, Mohamed A.; Afshan, Sheida; Atar, Muhammed; Cunningham, Lee S.; Foster, Andrew S. J. (Elsevier Sci Ltd, 2023)
This paper presents the results from a programme of elevated temperature tests focussing on the tensile behaviour of austenitic stainless steel bolts of grade A2-80 and A4-70. The tensile tests were carried out on bolt assemblies in the temperature range of 20 degrees C and 900 degrees C under a steady-state approach. Following the tests, a suite of tensile strength reduction factors were derived and these were compared with the existing bolt reduction factors proposed in the literature along with the codified values for equivalent stainless steel plate materials. The comparisons reveal that the manufacturing process of the stainless steel bolt, particularly the nature of thread rolling, can significantly affect their fire performance. For example, the present study reported a reduction factor of 0.098 for A4-70 at 800 degrees C as opposed to 0.176 (80% higher) and 0.34 (250% higher) for a bolt formed through a different manufacturing process and equivalent stainless steel plate materials, respectively. It was also concluded that while both the tensile strength and the ductility of stainless steel bolts gradually decrease with increasing temperature, stainless steel bolts retain a higher portion of their room temperature tensile strength compared with equivalent high strength carbon steel bolts beyond high temperatures of 450 degrees C for A2-80 bolts and 400 degrees C for A4-70 bolts.
Keywords: Elevated temperatures; Fire; Structural bolts; Stainless steel; Strength reduction factors